Composite fluorine removal agent, preparation method thereof and application of composite fluorine removal agent in reduction of fluorine impurity content in ionic rare earth mineral product
A composite defluorinating agent using carboxymethylated activated carbon and modified montmorillonite addresses inefficiencies in existing methods, achieving high fluorine removal rates and environmental benefits in rare earth mineral processing.
Patent Information
- Application Number
- CN202411326974.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for reducing fluorine content in rare earth carbonate products, such as ammonium salt and resin adsorption, face challenges like short service life, high cost, and complexity, while traditional composite defluorinating agents are costly and inefficient, leading to environmental and quality issues in glass manufacturing.
A composite defluorinating agent composed of carboxymethylated activated carbon and modified montmorillonite, prepared through specific steps of carboxymethylation, alkali activation, and aminosilane coupling, enhances adsorption capacity and stability, effectively removing fluorine from rare earth mineral products.
The composite agent achieves a fluorine removal rate of less than 0.1% in rare earth mineral products, improving product quality and reducing environmental impact, with a cost-effective and efficient process that simplifies operations and reduces production costs.
Smart Images

Figure CN119186493A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorine removal, and specifically relates to a composite defluorinating agent, a preparation method thereof and an application thereof in reducing the fluorine impurity content in ionic rare earth mineral products. Background Art
[0002] In the process of deep processing of ion-adsorption rare earth ores, although the fluorine (F) content of the rare earth carbonate product obtained after the separation of light rare earth and heavy rare earth does not constitute an excessive problem according to national standards and industry specifications, this subtle difference is crucial in specific application fields, especially in the glass manufacturing industry. Rare earth carbonate is the core material for the preparation of rare earth metal oxides and rare earth metal salts in the glass matrix. Once its fluorine content exceeds the fine standard, it will significantly weaken the acid and alkali resistance of the final glass product, affecting product quality and market competitiveness.
[0003] As the production cost of light rare earth products continues to rise, if the fluorine content in rare earth carbonate is not properly controlled, it will not only increase the environmental burden of enterprises, but also bury the hidden danger of product quality crisis. Therefore, how to effectively reduce the fluorine content in rare earth carbonate has become a technical problem that needs to be solved urgently.
[0004] At present, the purification methods of rare earth carbonate include physical method, chemical precipitation method and adsorption method, among which the adsorption method stands out with its successful cases of industrial application. In the subdivision of adsorption method, ammonium salt method and resin adsorption method are particularly common. However, although the resin adsorption method is effective, it faces challenges such as short service life (usually 2 to 3 days), complex process, high cost and difficulty in recovery. The cost increases significantly under long-term operation. In contrast, the ammonium salt method has emerged with its lower cost advantage. + With F - The reaction generates ammonium fluoride for separation, while NH + It can also absorb some rare earth fluorides and SO4 2- Although this method has problems such as the introduction of additional impurities and the complexity of subsequent impurity removal, its cost advantage and the recyclability of ammonia water still make it have certain application potential.
[0005] A Chinese patent application document (publication number: CN117247092A) discloses a defluorinating agent for treating fluorine-containing wastewater and a preparation method thereof, wherein the defluorinating agent is prepared using chitosan as a biological molecular skeleton and magnesium salt, titanium salt, zirconium salt, aluminum salt, iron salt, rare earth material, and organic material as a blended raw material; wherein the mass ratio of magnesium salt: titanium salt: zirconium salt: aluminum salt: iron salt: rare earth material: organic material: chitosan is: 1-30: 1-30: 2-20: 2-10: 2-10: 20-50: 2-10: 1-10. This invention is based on the existing composite defluorinating agent, and additional magnesium salt, titanium salt, zirconium salt and organic material are added to prepare a new defluorinating agent, which has good stability and a wide range of action, but has problems such as high cost.
[0006] See Figure 1 Looking back at the traditional production process of rare earth mineral products, when the mother liquor was removed from impurities, the pH value was adjusted, and the Al2O3 content in the rare earth carbonate product was finally reduced from 3.5% to about 2.5%, which greatly improved the quality of the product. However, the fluorine content in the supernatant of the straw salt precipitation after acid dissolution increased. It is speculated that the fluorine in the slag combined with hydrogen ions during sulfuric acid dissolution to form HF, which dissolved out.
[0007] The table below shows the fluorine content of a sample from the original process flow of the hydrometallurgical workshop.
[0008]
[0009] As can be seen from the table above, the fluorine content in the supernatant of the straw salt precipitation is nearly 100 times higher than that in the supernatant of the carbon precipitation. The supernatant needs to be recycled and re-entered into the system, and directly used to prepare the leaching solution, which causes the fluorine element to accumulate between the mother liquor and the rare earth mineral products, and the fluorine content continues to rise. At the same time, such a high fluorine content enters the mountain, which will cause serious environmental problems in the long run. If it can be cut off from the source, that is, the fluorine in the supernatant of the straw salt precipitation can be effectively removed and prevented from entering the leaching process, the trend of increasing fluorine content in the mother liquor and rare earth mineral products can be fundamentally curbed. The proposal of this idea marks a new round of exploration and pursuit of fluorine removal technology, aiming to achieve a more environmentally friendly and efficient rare earth mineral production process. Summary of the invention
[0010] In order to solve the problems of the background technology, the present invention provides a composite defluorinating agent, a preparation method thereof and an application thereof in reducing the fluorine impurity content in ionic rare earth mineral products.
[0011] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0012] A composite defluoridating agent comprises an active component, wherein the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 8-12:1.
[0013] The present invention also provides a method for preparing a composite defluorinating agent, comprising the following steps:
[0014] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0015] (2) adding magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 50-70° C. for 2-4 hours to obtain acylated montmorillonite;
[0016] (3) mixing the acylated montmorillonite with an aminosilane coupling agent to obtain the target product, modified montmorillonite;
[0017] (4) Carboxymethylated activated carbon and modified montmorillonite are mixed in a mass ratio of 8-12:1 to prepare a composite defluorination agent.
[0018] Preferably, the method for preparing the alkali-activated neutral montmorillonite in step (2) comprises the following steps:
[0019] (2-1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 8-10, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite;
[0020] (2-2) Alkali-activated montmorillonite is mixed with a sodium silicate aqueous solution in a mass ratio of 1:(3-5), stirred evenly, and then thermally activated at 70-80° C. for 1-2 h to obtain alkali-activated neutral montmorillonite.
[0021] More preferably, the weight ratio of montmorillonite to sodium hydroxide in step (2-1) is 10:(4-6).
[0022] More preferably, the mass ratio of the alkali-activated montmorillonite to the sodium silicate aqueous solution in step (2-2) is 1:(3-5).
[0023] Still more preferably, the mass fraction of the sodium silicate aqueous solution is 10-15%.
[0024] Preferably, the magnesium chloride solution in step (2) is obtained by dissolving 5-10% by mass of magnesium chloride in a sodium hydroxide aqueous solution with a pH of 8-10.
[0025] Preferably, in step (3), the acylated montmorillonite and the aminosilane coupling agent are mixed in a mass ratio of 10:1-3.
[0026] More preferably, the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane.
[0027] The present invention also provides an application of a composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products, comprising the following steps:
[0028] (1) Filling the filter column with the composite defluorinating agent;
[0029] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0030] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0031] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0032] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0033] (6) treating the mother liquor obtained in step (5) to obtain a rare earth mineral product with a low fluorine content
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] (1) The present invention has made significant progress in the frontier field of materials science. Through a carefully designed composite material strategy, it creatively combines carboxylated surface functionalized activated carbon with carefully modified amino-modified layered silicate clay (i.e., montmorillonite), achieving an unprecedented performance leap. Activated carbon, a traditional and powerful adsorption material, is endowed with abundant oxygen-containing functional groups on its surface through carboxylation treatment in the present invention. This design not only optimizes the impurity removal efficiency, but also significantly improves the overall adsorption capacity by enhancing the adsorption strength, so that the purification capacity in complex environments reaches a new height. Montmorillonite, a natural layered silicate mineral, has been rejuvenated under the modification process of the present invention. By introducing aminosilane coupling agents, amino groups are cleverly "grafted" onto the surface of montmorillonite. These groups connect montmorillonite and activated carbon like bridges, making the interaction between the two reach an unprecedented level of closeness. This molecular-level combination not only greatly improves the compatibility between montmorillonite and activated carbon, but also promotes the stability of the internal structure of the composite material, ensuring the reliability and durability of long-term use.
[0036] (2) The present invention uses carboxymethylated activated carbon and modified montmorillonite in a weight ratio of 8-12:1 to obtain a composite defluoridation agent, which has strong surface acidification and layered metal ion complexing interactions with the modified layered montmorillonite. At the same time, the modified montmorillonite has a special ion adsorption defluoridation process. When prepared into a composite adsorbent, it has a strong interlayer interaction with the modified montmorillonite to improve the defluoridation effect; at the same time, the carboxymethylated activated carbon has multiple functions such as complexation and adsorption, and provides a large specific surface area, which greatly improves the defluoridation effect. The existing montmorillonite or activated carbon is used as a single component to prepare a single-component adsorbent, which does not have layered metal ion cations and intralayer adsorption characteristics and multiple adsorption groups. At the same time, there is no adsorption site on the surface of the activated carbon. The single activated carbon or montmorillonite has a low defluoridation efficiency in rare earth products, which is only 10-30%. By using the technical approach provided by the present invention to process rare earth carbonate products, the fluorine removal rate is high during the fluorine removal treatment process, and the fluorine content of the obtained rare earth mineral product is less than 0.1%. At the same time, the content of other impurities is also reduced, meeting the requirements of the fluorine ion index of high-purity rare earth products, improving the quality of rare earth mineral products, and increasing the added value, which is an effect that cannot be achieved by the existing technology.
[0037] (3) The composite defluorinating agent carefully developed by the present invention has set a new benchmark in the field of environmental protection with its excellent performance. Its most striking feature is its ultra-large specific surface area. This design ingenuity greatly enhances the adsorption capacity of the material, making the defluorination process as efficient and thorough as a sponge absorbing water. Compared with traditional defluorinating agents, the efficiency of the present invention has achieved a qualitative leap. It not only significantly improves the processing speed, but also shows excellent stability while maintaining high efficiency, ensuring good performance in long-term applications. What is even more exciting is that through sophisticated formula optimization and innovation in production processes, the cost of the defluorinating agent of the present invention has been greatly reduced, paving the way for widespread application, so that both large and small enterprises can easily afford it and enjoy the environmental protection dividends brought by scientific and technological progress.
[0038] (4) In the field of treatment of the supernatant of straw salt precipitation, the application process of the present invention is undoubtedly a revolutionary breakthrough. This process has completely overturned the cumbersome and inefficient traditional defluorination operation with its efficient, continuous and stable operation characteristics. Through a carefully designed treatment process, precise control of the treatment of the straw salt precipitation supernatant is achieved, ensuring the continuous stability of the treatment effect. This innovation not only greatly simplifies the defluorination operation process and reduces the need for manual intervention, but also significantly reduces the technical difficulty of defluorination work, making it easy for even non-professionals to get started and effectively improving work efficiency. At the same time, the significant reduction in costs has injected strong impetus into the green development of enterprises and demonstrated the huge potential of scientific and technological innovation in the field of environmental protection.
[0039] (5) The application process of the present invention is used to treat the supernatant of the straw salt precipitation, and its defluorination effect is excellent. The fluorine content of the straw salt precipitation supernatant after fine treatment is so low that it is almost comparable to the supernatant in the workshop. This achievement not only reflects the profound attainments of the present invention in defluorination technology, but also opens up a new way for subsequent resource recycling. The enterprise can directly pump the treated clear liquid into the supernatant pool and seamlessly connect it to the preparation process of the leaching liquid without the need for additional cumbersome uphill water pump system, which not only saves equipment investment but also simplifies the operation process. What is even more gratifying is that the optimization and integration of this series of processes enables the defluorination work to be completed independently within the workshop without external assistance, thereby greatly reducing the production cost of rare earth mineral products and enhancing the overall competitiveness of the enterprise. This series of significant improvements is undoubtedly a comprehensive upgrade and transcendence of the traditional defluorination process, providing strong technical support for enterprises to achieve green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the production flow chart of traditional rare earth mineral products.
[0042] Figure 2 This is a production flow chart of rare earth mineral products with improved process of the present invention. DETAILED DESCRIPTION
[0043] In order to facilitate a better understanding of the present invention, the following examples are used to illustrate the present invention. These examples belong to the protection scope of the present invention, but do not limit the protection scope of the present invention.
[0044] In an embodiment of the present invention, the composite defluoridating agent comprises an active component, and the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 8-12:1.
[0045] The preparation method of the composite defluorinating agent comprises the following steps:
[0046] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0047] (2) adding a magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 50-70° C. for 2-4 hours to obtain an acylated montmorillonite; the magnesium chloride solution is obtained by dissolving 5-10% by mass magnesium chloride in a sodium hydroxide aqueous solution at a pH of 8-10;
[0048] (3) mixing the acylated montmorillonite and the aminosilane coupling agent in a mass ratio of 10:1-3 to obtain the target product modified montmorillonite, wherein the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane;
[0049] (4) Carboxymethylated activated carbon and modified montmorillonite are mixed in a mass ratio of 8-12:1 to prepare a composite defluorination agent.
[0050] The preparation method of the alkali-activated neutral montmorillonite comprises the following steps:
[0051] (1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 8-10, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; the weight ratio of the montmorillonite to the sodium hydroxide is 10:(4-6);
[0052] (2) Alkali-activated montmorillonite is mixed with a sodium silicate aqueous solution in a mass ratio of 1:(3-5), stirred evenly, and then thermally activated at 70-80° C. for 1-2 hours to obtain alkali-activated neutral montmorillonite; the mass fraction of the sodium silicate aqueous solution is 10-15%.
[0053] The preparation method of the carboxymethylated activated carbon comprises the following steps:
[0054] (1) Coal is heated to generate a mixed gas under the action of water vapor, and the mixed gas is passed from one end of the reaction tube to the other end through a carrier gas. The mixed gas is collected, cooled, and washed to form a liquid activated carbon solution. The activation temperature is 300-600°C and the activation time is 0.5-10h;
[0055] (2) heating the liquid activated carbon solution, evaporating the water therein, obtaining liquid hydrocarbons and waste liquid A by vacuum distillation, adding an activator to the liquid hydrocarbons in a nitrogen environment, activating them at a high temperature of 300-500° C. for 2-4 hours, and obtaining activated carbon;
[0056] (3) dissolving activated carbon in water to obtain an activated carbon aqueous solution, adjusting the pH of the activated carbon aqueous solution to 2-3 with dilute sulfuric acid, reacting for 2-4 hours, filtering, washing and removing sulfate ions in the activated carbon aqueous solution, and then drying to obtain surface-acidified activated carbon;
[0057] (4) Polyethylene oxide is mixed with 35-40% sodium hydroxide solution in a mass ratio of (1-5):100, condensed and refluxed, cooled and crystallized to obtain a mixture of polyoxyethylene ether and sodium hydroxide, and a 20-25% hydrochloric acid solution is continuously added to the mixture, stirred for 2-3 hours, filtered, and the filtrate is collected. The filtrate is heated to reflux for 1-2 hours, cooled, and a 30-36% NaOH solution is added until the pH of the filtrate is 8-11, and surface-acidified activated carbon is added. The mixture is stirred at 75-80°C for 1-1.5 hours and then allowed to stand at 0-3°C. After the standing is completed, the lower layer is centrifuged, washed and dried to obtain carboxymethylated activated carbon.
[0058] See Figure 2The use of the composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products comprises the following steps:
[0059] (1) Filling the filter column with the composite defluorinating agent;
[0060] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0061] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0062] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0063] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0064] (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
[0065] Technical principle of the present invention:
[0066] In the process of preparing alkali-activated neutral montmorillonite, each step is carefully designed to maximize the performance and defluorination ability of the material, achieving significant technological progress.
[0067] Interaction between montmorillonite and sodium hydroxide: As a natural layered silicate mineral, montmorillonite is rich in exchangeable cations such as calcium and magnesium between its layers and on its surface. Adding a sodium hydroxide aqueous solution with a pH of 8-10 and heating it not only effectively adjusts the pH environment of montmorillonite and promotes the replacement of interlayer cations, but also increases the specific surface area and pore structure of montmorillonite through alkaline corrosion, forming more active sites. This process significantly improves the adsorption capacity of montmorillonite for fluoride ions, laying a solid foundation for subsequent neutralization treatment.
[0068] Ratio of montmorillonite to sodium hydroxide: Strictly controlling the weight ratio of montmorillonite to sodium hydroxide (10:(4-6)) is the key to ensuring the effectiveness of alkali activation. Too much or too little sodium hydroxide will affect the degree of structural change of montmorillonite, thereby affecting its adsorption performance. The appropriate ratio can maximize the activation of montmorillonite while avoiding structural damage caused by excessive erosion.
[0069] Introduction and thermal activation of sodium silicate: Sodium silicate aqueous solution (mass fraction 10-15%) as a silicon source is mixed with montmorillonite after alkali activation in a specific ratio, and thermal activation (70-80°C) further promotes the uniform deposition of silicon on the surface of montmorillonite to form an aluminosilicate complex. This complex not only enhances the structural stability of montmorillonite, but also optimizes the adsorption mechanism of fluoride ions through its unique surface chemical properties, realizes the transition from alkaline to neutral, and broadens the scope of application.
[0070] Fine control of the amount of sodium silicate: The amount of sodium silicate directly affects the quality of the formation of aluminosilicate complexes on the surface of montmorillonite. Adding an appropriate amount can significantly improve the adsorption efficiency and stability of the material, while too much may cause surface blockage and reduce effective adsorption sites; too little will not form enough complexes, affecting the defluorination effect.
[0071] Optimization and necessity of irreversible process steps:
[0072] Fixed order of steps: first, montmorillonite is activated with alkali, then mixed with sodium silicate for thermal activation. This order is a scientific arrangement based on the transformation of material properties and chemical reaction kinetics. Changing the steps will result in insufficient changes in the material structure and failure to form an ideal adsorption surface, thus significantly reducing the defluorination efficiency.
[0073] Optimization of process parameters: The temperature, time and other parameters in each step are carefully optimized to achieve the best activation effect and adsorption performance. For example, the selection of thermal activation temperature and time should ensure that sodium silicate and montmorillonite react fully, while avoiding material sintering caused by high temperature. The fine control of these parameters is an important guarantee for achieving significant technological progress.
[0074] In-depth analysis and technological innovation in the preparation of carboxymethylated activated carbon:
[0075] Preparation of coal-based activated carbon: By high-temperature activation of coal powder, it reacts with water vapor to produce activated carbon with a high specific surface area and porous structure. This process not only removes impurities in the coal, but also significantly improves the adsorption performance of the activated carbon.
[0076] Surface acidification treatment: Use dilute sulfuric acid to adjust the pH of the activated carbon aqueous solution to introduce acidic functional groups such as carboxyl groups onto the surface of the activated carbon, thereby enhancing its electrostatic attraction to fluoride ions and improving the adsorption selectivity.
[0077] Carboxymethylation modification: Through the complex reaction of polyethylene oxide with sodium hydroxide and hydrochloric acid, a modifier containing carboxymethyl groups is prepared, which is then combined with surface acidified activated carbon to achieve deep modification of activated carbon. Carboxymethylation not only increases the hydrophilicity and charge density of the activated carbon surface, but also forms more fluoride ion adsorption sites, significantly improving the defluorination efficiency.
[0078] Optimization of raw material dosage and process parameters:
[0079] Precise control of raw material ratio: Whether it is coal powder activation, acidification or carboxymethylation modification, the raw material ratio is strictly calculated to ensure that each step can achieve the best effect. For example, the ratio of polyethylene oxide to sodium hydroxide directly affects the generation efficiency and quality of the modifier, which in turn affects the modified effect of activated carbon.
[0080] Fine adjustment of process parameters: from the activation temperature and time of coal powder, to the pH and reaction time of acidification treatment, to the temperature and stirring time in carboxymethylation modification, the setting of each parameter is based on a large amount of experimental data and theoretical analysis, aiming to maximize the defluorination performance.
[0081] In the process of preparing alkali-activated neutral montmorillonite and carboxymethylated activated carbon, each step and each raw material plays an indispensable role. The synergistic effect between them not only improves the adsorption performance of the materials, but also achieves significant technological progress. At the same time, precise control of raw material dosage and optimization of process parameters are also the key to ensuring product quality and stable performance.
[0082] The composite defluoridation agent of the present invention, as an innovative technological achievement, has its core in the carefully designed active component composition and the fine control of its preparation process:
[0083] 1. Carboxymethylated activated carbon: As one of the main components of composite defluoridation agents, carboxymethylated activated carbon is modified by carboxymethylation, which not only increases the specific surface area and porosity of activated carbon, but also introduces abundant carboxyl functional groups. These functional groups have a strong adsorption capacity for fluoride ions, and effectively capture and fix fluoride substances in water through electrostatic action, ion exchange and surface complexation.
[0084] 2. Modified montmorillonite: Montmorillonite is a natural layered silicate mineral. After alkali activation, acylation and reaction with aminosilane coupling agents (such as 3-aminopropyl-trimethoxysilane), its surface properties change significantly. Acylation enhances the hydrophilicity and interlayer exchange capacity of montmorillonite, while the introduction of aminosilane coupling agents further improves its surface activity and selective adsorption capacity for fluoride ions. The modified montmorillonite and carboxymethylated activated carbon work synergistically to achieve efficient removal of fluoride ions through interlayer adsorption, surface complexation and molecular sieve effect.
[0085] Necessity and importance of controlling the dosage of composite defluorination agent raw materials:
[0086] Precise control of the amount of raw materials is the key to ensuring the stable and efficient performance of composite defluoridation agents. The mass ratio of carboxymethylated activated carbon to modified montmorillonite is controlled in the range of 8-12:1, which is the best ratio obtained after multiple experimental optimizations. Too high or too low a ratio may affect the adsorption effect: too much activated carbon may lead to waste of adsorption sites, while too much montmorillonite may reduce the overall adsorption rate and capacity. In addition, strict control of parameters such as the concentration of magnesium chloride solution, reaction temperature and time are also necessary conditions to ensure the excellent performance of modified montmorillonite.
[0087] The preparation steps of composite defluorination agent cannot be changed and the necessity of optimizing process parameters:
[0088] The steps for preparing the composite defluoridation agent are scientifically designed and each step is closely related and cannot be replaced at will. First, the carboxymethylation modification of activated carbon provides abundant active sites for subsequent adsorption; then, the acylation and modification of montmorillonite enhance its adsorption performance; finally, the scientific mixing of the two achieves complementary advantages and forms a powerful defluoridation system. The replacement or omission of any step may destroy this synergistic effect and affect the defluoridation effect.
[0089] At the same time, optimizing process parameters such as reaction temperature, time, solution pH, etc. is crucial to improving product performance. For example, appropriately increasing the reaction temperature can accelerate the reaction process, but too high a temperature may lead to more side reactions; extending the reaction time is conducive to a more complete reaction, but too long a time may increase energy consumption and costs. Therefore, by finely controlling these parameters, production efficiency and economic benefits can be maximized while ensuring product quality.
[0090] In summary, the composite defluoridation agent of the present invention has achieved significant progress in removing fluorine substances from water bodies through a carefully designed active component composition and a finely controlled preparation process. Its high efficiency and stable performance not only meets the urgent demand for efficient defluoridation technology in the field of environmental protection, but also provides new ideas and methods for the development of water treatment technology.
[0091] In order to make the present invention more fully disclosed, it is described below through more specific embodiments.
[0092] Example 1
[0093] A composite defluoridating agent comprises an active component, wherein the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 8.2:1.
[0094] The preparation method of the composite defluorinating agent comprises the following steps:
[0095] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0096] (2) adding a magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 50° C. for 4 hours to obtain an acylated montmorillonite; the magnesium chloride solution is obtained by dissolving 5.2% magnesium chloride by mass in a sodium hydroxide aqueous solution at a pH of 8;
[0097] (3) mixing the acylated montmorillonite and the aminosilane coupling agent in a mass ratio of 10:1 to obtain the target product modified montmorillonite, wherein the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane;
[0098] (4) Carboxymethylated activated carbon and modified montmorillonite were mixed in a mass ratio of 8.2:1 to prepare a composite defluorination agent.
[0099] The preparation method of the alkali-activated neutral montmorillonite comprises the following steps:
[0100] (1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 8, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; the weight ratio of the montmorillonite to the sodium hydroxide is 10:4;
[0101] (2) Alkali-activated montmorillonite was mixed with a sodium silicate aqueous solution in a mass ratio of 1:3, stirred evenly, and then thermally activated at 72° C. for 2 h to obtain alkali-activated neutral montmorillonite; the mass fraction of the sodium silicate aqueous solution was 10.2%.
[0102] The preparation method of the carboxymethylated activated carbon comprises the following steps:
[0103] (1) Coal is heated and reacted with water vapor to generate a mixed gas, which is passed from one end of a reaction tube to the other end through a carrier gas. The mixed gas is collected, cooled, and washed to form a liquid activated carbon solution. The activation temperature is 350°C and the activation time is 9 hours.
[0104] (2) heating the liquid activated carbon solution to evaporate the water therein, and obtaining liquid hydrocarbons and waste liquid A by vacuum distillation. Adding an activator (ZnCl2) to the liquid hydrocarbons in a nitrogen environment, activating them at a high temperature of 320°C for 4 hours, thereby obtaining activated carbon;
[0105] (3) dissolving activated carbon in water to obtain an activated carbon aqueous solution, adjusting the pH of the activated carbon aqueous solution to 2.3 with dilute sulfuric acid, reacting for 4 hours, filtering, washing and removing sulfate ions in the activated carbon aqueous solution, and then drying to obtain surface-acidified activated carbon;
[0106] (4) Polyethylene oxide and 36% sodium hydroxide solution are mixed in a mass ratio of 1.3:100, condensed and refluxed, cooled and crystallized to obtain a mixture of polyoxyethylene ether and sodium hydroxide, and a 21% hydrochloric acid solution is continuously added to the mixture. After stirring for 3 hours, the mixture is filtered and the filtrate is taken. The filtrate is heated to reflux for 1 hour, and after cooling, a 32% NaOH solution is added until the pH value of the filtrate is 8. Surface-acidified activated carbon is added, and the mixture is stirred at 76°C for 1.5 hours and then allowed to stand at 1°C. After the standing is completed, the lower layer of material is removed by centrifugation, and after washing and drying, carboxymethylated activated carbon is obtained.
[0107] The application of the composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products comprises the following steps:
[0108] (1) Filling the filter column with the composite defluorinating agent;
[0109] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0110] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0111] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0112] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0113] (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
[0114] Example 2
[0115] A composite defluoridating agent comprises an active component, wherein the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 10.3:1.
[0116] The preparation method of the composite defluorinating agent comprises the following steps:
[0117] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0118] (2) adding a magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 62° C. for 3 h to obtain an acylated montmorillonite; the magnesium chloride solution is obtained by dissolving 8.5% by mass of magnesium chloride in a sodium hydroxide aqueous solution at a pH of 9;
[0119] (3) mixing the acylated montmorillonite and the aminosilane coupling agent in a mass ratio of 10:2 to obtain the target product modified montmorillonite, wherein the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane;
[0120] (4) Carboxymethylated activated carbon and modified montmorillonite were mixed in a mass ratio of 10.3:1 to prepare a composite defluorination agent.
[0121] The preparation method of the alkali-activated neutral montmorillonite comprises the following steps:
[0122] (1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 9, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; the weight ratio of the montmorillonite to the sodium hydroxide is 10:5;
[0123] (2) Alkali-activated montmorillonite was mixed with a sodium silicate aqueous solution in a mass ratio of 1:4.2, stirred evenly, and then thermally activated at 76° C. for 1.5 h to obtain alkali-activated neutral montmorillonite; the mass fraction of the sodium silicate aqueous solution was 13%.
[0124] The preparation method of the carboxymethylated activated carbon comprises the following steps:
[0125] (1) Coal is heated and reacted with water vapor to generate a mixed gas, which is passed from one end of a reaction tube to the other end through a carrier gas. The mixed gas is collected, cooled, and washed to form a liquid activated carbon solution. The activation temperature is 500°C and the activation time is 6 hours.
[0126] (2) heating the liquid activated carbon solution to evaporate the water therein, and obtaining liquid hydrocarbons and waste liquid A by vacuum distillation. Adding an activator (ZnCl2) to the liquid hydrocarbons in a nitrogen environment, activating them at a high temperature of 420°C for 3 hours, thereby obtaining activated carbon;
[0127] (3) dissolving activated carbon in water to obtain an activated carbon aqueous solution, adjusting the pH of the activated carbon aqueous solution to 2.5 with dilute sulfuric acid, reacting for 3 hours, filtering, washing and removing sulfate ions in the activated carbon aqueous solution, and then drying to obtain surface-acidified activated carbon;
[0128] (4) Polyethylene oxide and 38% sodium hydroxide solution are mixed in a mass ratio of 3:100, condensed and refluxed, cooled and crystallized to obtain a mixture of polyoxyethylene ether and sodium hydroxide, and a 22% hydrochloric acid solution is continuously added to the mixture. After stirring for 2.6 hours, the mixture is filtered and the filtrate is taken. The filtrate is heated to reflux for 1.4 hours, and after cooling, a 35% NaOH solution is added until the pH of the filtrate is 10. Surface-acidified activated carbon is added, and the mixture is stirred at 78°C for 1.2 hours and then allowed to stand at 0°C. After the standing is completed, the lower layer of material is removed by centrifugation, and after washing and drying, carboxymethylated activated carbon is obtained.
[0129] The application of the composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products comprises the following steps:
[0130] (1) Filling the filter column with the composite defluorinating agent;
[0131] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0132] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0133] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0134] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0135] (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
[0136] Example 3
[0137] A composite defluoridating agent comprises an active component, wherein the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 9:1.
[0138] The preparation method of the composite defluorinating agent comprises the following steps:
[0139] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0140] (2) adding a magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 56° C. for 3.5 hours to obtain an acylated montmorillonite; the magnesium chloride solution is obtained by dissolving 7% by mass magnesium chloride in a sodium hydroxide aqueous solution at a pH of 8;
[0141] (3) mixing the acylated montmorillonite and the aminosilane coupling agent in a mass ratio of 10:1.5 to obtain the target product modified montmorillonite, wherein the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane;
[0142] (4) Carboxymethylated activated carbon and modified montmorillonite are mixed in a mass ratio of 9:1 to prepare a composite defluorination agent.
[0143] The preparation method of the alkali-activated neutral montmorillonite comprises the following steps:
[0144] (1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 8, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; the weight ratio of the montmorillonite to the sodium hydroxide is 10:4.5;
[0145] (2) Alkali-activated montmorillonite was mixed with a sodium silicate aqueous solution in a mass ratio of 1:3.6, stirred evenly, and then thermally activated at 73° C. for 2 h to obtain alkali-activated neutral montmorillonite; the mass fraction of the sodium silicate aqueous solution was 12%.
[0146] The preparation method of the carboxymethylated activated carbon comprises the following steps:
[0147] (1) Coal is heated and reacted with water vapor to generate a mixed gas, which is passed from one end of a reaction tube to the other end through a carrier gas. The mixed gas is collected, cooled, and washed to form a liquid activated carbon solution. The activation temperature is 400°C and the activation time is 8 hours.
[0148] (2) heating the liquid activated carbon solution to evaporate the water therein, obtaining liquid hydrocarbons and waste liquid A by vacuum distillation, adding an activator (ZnCl2) to the liquid hydrocarbons in a nitrogen environment, and activating them at a high temperature of 400°C for 3 hours to obtain activated carbon;
[0149] (3) dissolving activated carbon in water to obtain an activated carbon aqueous solution, adjusting the pH of the activated carbon aqueous solution to 2 with dilute sulfuric acid, reacting for 4 hours, filtering, washing and removing sulfate ions in the activated carbon aqueous solution, and then drying to obtain surface-acidified activated carbon;
[0150] (4) Polyethylene oxide and 38% sodium hydroxide solution are mixed in a mass ratio of 4:100, condensed and refluxed, cooled and crystallized to obtain a mixture of polyoxyethylene ether and sodium hydroxide, and a 23% hydrochloric acid solution is added to the mixture. After stirring for 2.5 hours, the mixture is filtered and the filtrate is taken. The filtrate is heated to reflux for 1.8 hours, and after cooling, a 34% NaOH solution is added until the pH of the filtrate is 10. Surface-acidified activated carbon is added, and the mixture is stirred at 76°C for 1 hour and allowed to stand at 3°C. After the standing is completed, the lower layer is centrifuged, washed and dried to obtain carboxymethylated activated carbon.
[0151] The application of the composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products comprises the following steps:
[0152] (1) Filling the filter column with the composite defluorinating agent;
[0153] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0154] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0155] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0156] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0157] (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
[0158] Example 4
[0159] A composite defluoridating agent comprises an active component, wherein the active component is obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 12:1.
[0160] The preparation method of the composite defluorinating agent comprises the following steps:
[0161] (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon;
[0162] (2) adding a magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 68° C. for 2 h to obtain an acylated montmorillonite; the magnesium chloride solution is obtained by dissolving 10% by mass magnesium chloride in a sodium hydroxide aqueous solution at a pH of 10;
[0163] (3) mixing the acylated montmorillonite and the aminosilane coupling agent in a mass ratio of 10:2.7 to obtain the target product modified montmorillonite, wherein the aminosilane coupling agent is 3-aminopropyl-trimethoxysilane;
[0164] (4) Carboxymethylated activated carbon and modified montmorillonite are mixed in a mass ratio of 12:1 to prepare a composite defluorination agent.
[0165] The preparation method of the alkali-activated neutral montmorillonite comprises the following steps:
[0166] (1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 10, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; the weight ratio of the montmorillonite to the sodium hydroxide is 10:5.8;
[0167] (2) Alkali-activated montmorillonite is mixed with a sodium silicate aqueous solution in a mass ratio of 1:5, stirred evenly, and then thermally activated at 80° C. for 1 h to obtain alkali-activated neutral montmorillonite; the mass fraction of the sodium silicate aqueous solution is 15%.
[0168] The preparation method of the carboxymethylated activated carbon comprises the following steps:
[0169] (1) Coal is heated and reacted with water vapor to generate a mixed gas, which is passed from one end of a reaction tube to the other end through a carrier gas. The mixed gas is collected, cooled, and washed to form a liquid activated carbon solution. The activation temperature is 550°C and the activation time is 2 hours.
[0170] (2) heating the liquid activated carbon solution to evaporate the water therein, obtaining liquid hydrocarbons and waste liquid A by vacuum distillation, adding an activator (ZnCl2) to the liquid hydrocarbons in a nitrogen environment, and activating them at a high temperature of 500°C for 2 hours to obtain activated carbon;
[0171] (3) dissolving activated carbon in water to obtain an activated carbon aqueous solution, adjusting the pH of the activated carbon aqueous solution to 3 with dilute sulfuric acid, reacting for 2 hours, filtering, washing and removing sulfate ions in the activated carbon aqueous solution, and then drying to obtain surface-acidified activated carbon;
[0172] (4) Polyethylene oxide and 40% sodium hydroxide solution are mixed in a mass ratio of 3:100, condensed and refluxed, cooled and crystallized to obtain a mixture of polyoxyethylene ether and sodium hydroxide, and a 25% hydrochloric acid solution is added to the mixture. After stirring for 2 hours, the mixture is filtered and the filtrate is taken. The filtrate is heated to reflux for 1.5 hours, and after cooling, a 35% NaOH solution is added until the pH of the filtrate is 10. Surface-acidified activated carbon is added, and the mixture is stirred at 80°C for 1 hour and then allowed to stand at 1°C. After the standing is completed, the lower layer of material is removed by centrifugation, and after washing and drying, carboxymethylated activated carbon is obtained.
[0173] The application of the composite defluorinating agent in reducing the fluorine impurity content in ionic rare earth mineral products comprises the following steps:
[0174] (1) Filling the filter column with the composite defluorinating agent;
[0175] (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation;
[0176] (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant;
[0177] (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution;
[0178] (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor;
[0179] (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
[0180] Comparative Example 1
[0181] The defluorinating agent was prepared by the method of Example 2 in the Chinese patent application document "A defluorinating agent for treating fluorine-containing wastewater and its preparation method (publication number: CN117247092A)".
[0182] Comparative Example 2
[0183] Commercially available activated alumina was used.
[0184] Fluoride removal test of the supernatant of straw salt precipitation:
[0185] The supernatant of the straw salt precipitation was treated with the defluorination agents of Examples 1-4 and Comparative Examples 1-2 for defluorination, and the treatment effects are shown in the following table.
[0186]
[0187] It can be seen from the above table:
[0188] (1) In the process of further exploring the purification of the supernatant of the grass salt precipitation, the composite defluorinating agent designed by the present invention showed remarkable defluorination performance under the test of its Examples 1-4. These carefully proportioned composite defluorinating agents, through the synergistic effect of their unique chemical structure and physical properties, can efficiently and stably capture and remove fluoride ions in water, and the defluorination rate is steadily maintained at an excellent level of more than 97.90%. This achievement not only marks a significant improvement in the defluorination efficiency, but also broadens its scope of application.
[0189] (2) By analyzing the defluorination data of Examples 1-4 and Comparative Example 1 (i.e., the defluorination agent in the prior art), it can be clearly seen that the defluorination agent of the present invention has been improved in performance. Its excellent defluorination effect is not only better than the prior art, but also has an essential difference in the technical principle behind it. The defluorination agent of the present invention utilizes multiple mechanisms such as advanced surface adsorption, ion exchange and chemical reaction through innovative material selection and formula design to achieve efficient and accurate removal of fluoride ions. This technological innovation not only improves the defluorination efficiency, but also reduces the processing cost and reduces the generation of by-products, demonstrating the dual advantages of the present invention in environmental protection and resource utilization. Therefore, it can be clearly said that the defluorination technology of the present invention is significantly progressive and creative compared to the prior art (Comparative Example 1).
[0190] (3) Further comparing the defluorination effects of Examples 1-4 with Comparative Example 2 (using traditional defluorinators), the huge difference in data further highlights the superiority of the present invention. When traditional defluorinators are used to treat the supernatant of grass salt precipitation, their defluorination rate is often limited by their single defluorination mechanism and material properties, and can only reach 60.49%, which is difficult to meet the production requirements of rare earth mineral products. The composite defluorinator of the present invention, with its advanced composite formula and multiple defluorination mechanisms, has achieved an amazing performance of a fluorination rate that is stable at more than 97.90%. This significant performance improvement is not only a breakthrough in the bottleneck of the existing technology, but also an expansion of the boundaries of water treatment technology. It once again proves the unique value of the defluorination technology of the present invention in treating complex water bodies and improving water quality safety, as well as its significant advancement and creativity compared to the existing technology (Comparative Example 2), injecting new vitality and hope into the development of the water treatment industry.
[0191] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite defluorinating agent, characterized in that: The invention comprises active components, wherein the active components are obtained by mixing carboxymethylated activated carbon and modified montmorillonite in a mass ratio of 8-12:
1.
2. A method for preparing a composite defluorinating agent according to claim 1, characterized in that: The steps include: (1) Modifying activated carbon by carboxymethylation to obtain carboxymethylated activated carbon; (2) adding magnesium chloride solution to the alkali-activated neutral montmorillonite and reacting at 50-70° C. for 2-4 hours to obtain acylated montmorillonite; (3) mixing the acylated montmorillonite with an aminosilane coupling agent to obtain the target product, modified montmorillonite; (4) Carboxymethylated activated carbon and modified montmorillonite are mixed in a mass ratio of 8-12:1 to prepare a composite defluorination agent.
3. The method for preparing the composite defluorinating agent according to claim 2, characterized in that: The method for preparing the alkali-activated neutral montmorillonite in step (2) comprises the following steps: (2-1) adding montmorillonite to a sodium hydroxide aqueous solution with a pH of 8-10, heating for reaction, and centrifuging, washing, and vacuum drying the resulting suspension to obtain alkali-activated montmorillonite; (2-2) Alkali-activated montmorillonite is mixed with a sodium silicate aqueous solution in a mass ratio of 1:(3-5), stirred evenly, and then thermally activated at 70-80° C. for 1-2 h to obtain alkali-activated neutral montmorillonite.
4. The method for preparing the composite defluorinating agent according to claim 3, characterized in that: The weight ratio of montmorillonite to sodium hydroxide in step (2-1) is 10:(4-6).
5. The method for preparing the composite defluorinating agent according to claim 3, characterized in that: The mass ratio of the alkali-activated montmorillonite to the sodium silicate aqueous solution in step (2-2) is 1:(3-5).
6. The method for preparing the composite defluorinating agent according to claim 5, characterized in that: The mass fraction of the sodium silicate aqueous solution is 10-15%.
7. The method for preparing the composite defluorinating agent according to claim 2, characterized in that: The magnesium chloride solution in step (2) is obtained by dissolving magnesium chloride with a mass fraction of 5-10% in a sodium hydroxide aqueous solution with a pH of 8-10.
8. The method for preparing the composite defluorinating agent according to claim 2, characterized in that: In step (3), the acylated montmorillonite and the aminosilane coupling agent are mixed in a mass ratio of 10:1-3.
9. The method for preparing the composite defluorinating agent according to claim 8, characterized in that: The aminosilane coupling agent is 3-aminopropyl-trimethoxysilane.
10. Use of the composite defluorinating agent prepared according to the method according to any one of claims 2 to 9 in reducing the fluorine impurity content in ionic rare earth mineral products, characterized in that: The following steps are involved: (1) Filling the filter column with the composite defluorinating agent; (2) collecting the supernatant after the rare earth is precipitated with oxalic acid to obtain the supernatant of the oxalic acid precipitation; (3) passing the straw salt precipitation supernatant obtained in step (2) into the filter column of step (1) for defluorination, thereby obtaining a defluorinated straw salt precipitation supernatant; (4) pumping the defluorinated straw salt precipitation supernatant obtained in step (3) into a supernatant tank for preparing a leaching solution; (5) leaching rare earth ore with the leaching solution prepared in step (4) to obtain a mother liquor; (6) The mother liquor obtained in step (5) is treated to obtain a rare earth mineral product with a low fluorine content.
Citation Information
Patent Citations
Preparation method of porous activated carbon nanofiber-loaded montmorillonite fluoride-removing material
CN107159119A
Fluorine-containing sewage medicament as well as preparation method and application thereof
CN118084100A
Perfluoroalkyl and polyfluoroalkyl sorbent materials and methods of use
US20200316560A1
Method for removing polyfluorinated organic compounds from water by means of an adsorbent and regeneration of the latter
US20210346862A1
